Ice ingestion with a long rest interval increases the endurance exercise capacity and reduces the core temperature in the heat - Naito, T.; Iribe, Y.; Ogaki, T. (Journal of Physiological Anthropology, 2017)
Background: The timing in which ice before exercise should be ingested plays an important role in optimizing its success. However, the effects of differences in the timing of ice ingestion before exercise on cycling capacity, and thermoregulation has not been studied. The aim of the present study was to assess the effect of length of time after ice ingestion on endurance exercise capacity in the heat. Methods: Seven males ingested 1.25 g kg body mass-1 of ice (0.5 °C) or cold water (4 °C) every 5 min, six times. Under three separate conditions after ice or water ingestion ([1] taking 20 min rest after ice ingestion, [2] taking 5 min rest after ice ingestion, and [3] taking 5 min rest after cold water ingestion), seven physically active male cyclists exercised at 65% of their maximal oxygen uptake to exhaustion in the heat (35 °C, 30% relative humidity). Results: Participants cycled significantly longer following both ice ingestion with a long rest interval (46.0 ± 7.7 min) and that with a short rest interval (38.7 ± 5.7 min) than cold water ingestion (32.3 ± 3.2 min; both p < 0.05), and the time to exhaustion was 16% (p < 0.05) longer for ice ingestion with a long rest interval than that with a short rest interval. Ice ingestion with a long rest interval (-0.55 ± 0.07 °C; both p < 0.05) allowed for a greater drop in the core temperature than both ice ingestion with a short rest interval (-0.36 ± 0.16 °C) and cold water ingestion (-0.11 ± 0.14 °C). Heat storage under condition of ice ingestion with a long rest interval during the pre-exercise period was significantly lower than that observed with a short rest interval (-4.98 ± 2.50 W m-2; p < 0.05) and cold water ingestion (2.86 ± 4.44 W m-2). Conclusions: Therefore, internal pre-cooling by ice ingestion with a long rest interval had the greatest benefit on exercise capacity in the heat, which is suggested to be driven by a reduced rectal temperature and heat storage before the start of exercise.